Therapeutic effects of neuropeptide substance P coupled with self-assembled peptide nanofibers on the progression of osteoarthritis in a rat model - Kim, Sang Jun; Kim, Ji Eun; Kim, Su Hee; Kim, Sun Jeong; Jeon, Su Jeong; Kim, Soo Hyun; Jung, Youngmee (ELSEVIER SCI LTD, 2016)
Osteoarthritis (OA) is a progressively degenerative disease that is accompanied by articular cartilage deterioration, sclerosis of the underlying bone and ultimately joint destruction. Although therapeutic medicine and surgical treatment are done to alleviate the symptoms of OA, it is difficult to restore normal cartilage function. Mesenchymal stem cell (MSC) transplantation is one of the therapeutic trials for treating OA due to its potential, and many researchers have recently reported on the effects of MSCs associated with OA therapy. However, cell transplantation has limitations including low stem cell survival rates, limited stem cell sources and long-term ex vivo culturing. In this study, we evaluated the efficacy of neuropeptide substance P coupled with self-assembled peptide hydrogels in a rat knee model to prevent OA by mobilizing endogenous MSCs to the defect site. To assess the effect of the optimal concentration of SP, varying concentrations of bioactive peptides (substance P (SP) with self-assembled peptide (SAP)) were used to treat OA. OA was induced by unilateral anterior cruciate and medial collateral ligament transection of the knee joints. Forty rats were randomly allocated into 5 groups: SAP-0.5SP (17.5 mu g of SP), SAP-SP group (35 mu g of SP), SAP-2SP group (70 mu g of SP), SAP-SP-MSC group, and control group. At 2 weeks post-surgical induction of OA, each mixture was injected into the joint cavity of the left knee. Histologic examination, immunofluorescence staining, quantitative real time-polymerase chain reaction and micro-computed tomography analysis were done at 6 weeks post-surgical induction. As shown by our results, the SAP-SP hydrogel accelerated tissue regeneration by anti-inflammatory modulation shown by an anti-inflammation test using dot-blot in vitro. Additionally, the treatment of OA in the SAP-SP group showed markedly improved cartilage regeneration through the recruitment of MSCs. Thus, these cells could be infiltrating into the defect site for the regeneration of OA defects. In addition, from the behavioral studies on the rats, the number of rears significantly increased 2 and 4 weeks post-injection in all the groups. Our results show that bioactive peptides may have clinical potential for inhibiting the progression of OA as well as its treatment by recruiting autologous stem cells without cell transplantation. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: STEM-CELL THERAPY; MARROW STROMAL CELLS; RECRUITMENT; DELIVERY; CARTILAGE; TRANSPLANTATION; ANGIOGENESIS; ARTHRITIS; BEHAVIOR; PAIN